The Influence Of Capital Structure, Return On Assets And Company Size On Value Company On Company Manufacture - Debora Afrianti Silaen; Aswin Akbar (SEAN Institute, 2024)
Company value is very important for a company, because if the company value increases it can attract investors to invest their capital in the company. This research was conducted intended to find out How the influence of capital structure variables, return on assets and company size on company value. This research was conducted at Textile and Garment Sub-Sector Manufacturing Companies for the 2014-2023 period which are listed on the Indonesia Stock Exchange (BEI) with a population of 22 companies. Sampling was carried out using a purposive sampling technique and a sample of only 6 companies was obtained. The research uses a quantitative approach because it is presented numerically. The analytical method used in this research is descriptive statistics method. The data analysis technique used is the classical assumption test and multiple linear regression analysis using application SPSS version 22. The research results show that simultaneously (F test) Capital Structure, Return On Assets and Company Size have a significant effect on Company Value (Y). Partially (t test), namely Capital Structure (DER) has no significant effect on Company Value, Return on Assets (ROA) has no partial effect but has a significant value on Company Value and Company Size has no partial effect but has a significant value.